Handbook of tensile properties of textile and technical fibres - Bunsell, A. R. (Woodhead Publishing, 2009)
Fibres usually experience tensile loads whether they are used for apparel or technical structures. Their form, which is long and fine, makes them some of the strongest materials available as well as very flexible. This book provides a concise and authoritative overview of tensile behaviour of a wide range of both natural and synthetic fibres used both in textiles and high performance materials. After preliminary chapters that introduce the reader to tensile properties, failure and testing of fibres, the book is split into two parts. Part one examines tensile properties and failure of natural fibres, such as cotton, hemp, wool and silk. Part two discusses the tensile properties and failure of synthetic fibres ranging from polyamide, polyester and polyethylene fibres to carbon fibres. Many chapters also provide a general background to the fibre, including the manufacture, microstructure, factors that affect tensile properties as well as methods to improve tensile failure. With its distinguished editor and array of international contributors, Handbook of tensile properties of textile and technical fibres is an important reference for fibre scientists, textile technologists and engineers, as well as those in academia. Provides an overview of tensile behaviour of a wide range of both natural and synthetic fibresExamines tensile characterisitics, tensile failure of textiles fibres and factors that affect tensile propertiesDiscusses mircostructures and each type of fibre from manufacture to finished product.
"The Textile Institute."
Keywords: Textile fibers -- Mechanical properties.; Textile fibers, Synthetic -- Mechanical properties.; elektronické knihy; electronic books